Shoulder instability in athletes: principles of diagnosis and treatment [Sporcularda omuz instabilitesi: tani ve tedavi prensipleri.] - (:unkn) unknown (My University, 2005)
Shoulder complaints are one of the leading reasons for a doctor's visit in athletes involved in overhead activities, and among them, dislocation and subluxation are very frequent clinical presentations. Although diagnosis and management of shoulder problems are more clear-cut in traumatic cases, atraumatic cases may be quite troublesome. In order to facilitate the interval between the presentation of complaints and institution of appropriate treatment, many issues should be appreciated including the anatomy, etiology, pathogenesis, clinical evaluation, and treatment of shoulder disorders. This review aims to outline the current approach to shoulder problems arising from instability in the light of the most recent literature.